2016
DOI: 10.1016/j.jff.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Amaranth peptides with antithrombotic activity released by simulated gastrointestinal digestion

Abstract: Amaranth protein isolate was obtained and subjected to simulated gastrointestinal digestion to evaluate its potential antithrombotic activity. The protein isolate did not present fibrin clotting inhibition at the concentrations studied, whereas the hydrolysate (DH% = 51.1 ± 3.8%) exhibited inhibition of fibrin coagulation, showing a dose-response behaviour (IC50 = 0.23 ± 0.02 mg/mL), confirming that the enzymatic treatment was able to release bioactive peptides from amaranth proteins. A fraction with high anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Additionally, the absorption of the peptide fraction was analysed with an in vitro assay of peptide transport through intestinal epithelium. The authors observed that some peptides were able to cross the Caco2‐TC7 cell monolayer (Sabbione et al ., ). Antiplatelet peptides released by simulated gastrointestinal digestion of oat (IC 50 = 0.282 mg mL −1 ), barley (IC 50 = 0.290 mg mL −1 ) and buckwheat (IC 50 = 0.328 mg mL −1 ) flours have been reported by Yu et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, the absorption of the peptide fraction was analysed with an in vitro assay of peptide transport through intestinal epithelium. The authors observed that some peptides were able to cross the Caco2‐TC7 cell monolayer (Sabbione et al ., ). Antiplatelet peptides released by simulated gastrointestinal digestion of oat (IC 50 = 0.282 mg mL −1 ), barley (IC 50 = 0.290 mg mL −1 ) and buckwheat (IC 50 = 0.328 mg mL −1 ) flours have been reported by Yu et al .…”
Section: Introductionmentioning
confidence: 97%
“…In the study conducted by Sabbione et al . (), an amaranth protein isolate was obtained and subjected to simulated gastrointestinal digestion to evaluate its potential antithrombotic activity. The peptide fraction obtained from the amaranth protein hydrolysate exhibited higher antithrombotic activity (IC 50 = 0.07 ± 0.01 mg mL −1 ) (IC 50 – a sample concentration providing 50% inhibition) than protein hydrolysate (IC 50 = 0.23 ± 0.02 mg mL −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Calculations were made according to Sabbione et al . (). Digestion was performed in two independent trials per sample.…”
Section: Methodsmentioning
confidence: 97%
“…In particular, amaranth peptides have exerted various biological activities (Silva‐Sánchez et al ., ). In vitro and in vivo antithrombotic and antihypertensive activity of amaranth peptides has been previously described in our laboratory (Vecchi & Añón, ; Fritz et al ., ; Sabbione et al ., , ).…”
Section: Introductionmentioning
confidence: 99%
“…Guo and others () established the anti‐fatigue activity of peptides obtained after papain hydrolysis of sea horse protein extract. Sabbione and others () showed the antithrombotic activity of amaranth protein produced after imitation of gastrointestinal digestion, and they also detected that various peptides are capable to cross the Caco2‐TC7 cell monolayer. Alamdari and Ehsani () underlined the antimicrobial peptides obtained by hydrolysis of milk proteins using digestive proteases or by lactic acid bacteria fermentation.…”
Section: Protease Applicationsmentioning
confidence: 97%